Migrant deaths in the Arizona desert : la vida no vale nada - Fernández, Celestino; Finch, Jessie K.; Masterson-Algar, Araceli; Rubio-Goldsmith, Raquel (The University of Arizona Press, 2016)
"Migrant Deaths in the Arizona Desert addresses the tragic results of government policies on immigration. The contributors consist of a multidisciplinary group who are dedicated to the thousands of men, women, and children who have lost their lives while crossing the desert in search of a better life. Each chapter in this important new volume seeks answers to migrant deaths, speaking to the complexity of this tragedy via a range of community and scholarly approaches"--Provided by publisher